Big data analytics and knowledge discovery : 19th International Conference, DaWaK 2017, Lyon, France, August 28-31, 2017, Proceedings /: 19th International Conference, DaWaK 2017, Lyon, France, August 28-31, 2017, Proceedings. (2017) - Unknown
No abstract available